Pemasangan Panel Surya di Gereja Toraja Jemaat Lembah Kasih Ollon, Buakayu Kabupaten Tana Toraja - Simon Patabang; Jeremias Leda (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The need for electrical energy for the Toraja Church, Lembah Kasih Ollon Congregation, Buakayu is very important to meet the needs of lighting and sound systems in the church. The location of the church from the city of Makale is approximately 40 km and is located in a valley called the Ollon Valley. The location of the Church has not yet received PLN electricity network services. To meet electricity needs, solar cell-based electrical energy is provided. The function of the solar cell panel is to convert solar energy and then produce direct current electrical energy. Because the lights and sound systems require alternating current, the direct current obtained from the solar panels is converted into alternating current. With the installation of a 160 Wp solar panel, the electricity source at the Toraja Church, Ollon Buakayu Congregation is available, both during the day and at night. Thus, the lighting system and sound system in the church can work properly.